2019
DOI: 10.1080/09537104.2019.1680826
|View full text |Cite
|
Sign up to set email alerts
|

Platelet count and mean volume in acute stroke: a systematic review and meta-analysis

Abstract: Changes of mean platelet volume (MPV) and platelet count (PC) could be a marker or a predictor of acute stroke (AS). We conducted a systematic review and meta-analysis of the published literature on the reporting of MPV and PC in AS. Studies were included in accordance with Patient Population or Problem, Intervention, Comparison, Outcomes, and Setting framework. The PRISMA strategy was used to report findings. Risk of bias was assessed with the Newcastle-Ottawa Scale. We included 34 eligible articles retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 69 publications
1
27
0
1
Order By: Relevance
“…coronary artery disease or stroke), it does not surprise that there are relations between MPV and acute one-month mortality. In a recent meta-analysis by [27], the author describes the MPV being significantly higher in patients with stroke. Similarly, two other groups describe the MPV correlating with the prevalence and the prognosis of coronary artery disease [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…coronary artery disease or stroke), it does not surprise that there are relations between MPV and acute one-month mortality. In a recent meta-analysis by [27], the author describes the MPV being significantly higher in patients with stroke. Similarly, two other groups describe the MPV correlating with the prevalence and the prognosis of coronary artery disease [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…As these are frequently cardiovascular states (i.e., coronary artery disease or stroke), it does not surprise that there are relations between MPV and acute one-month mortality. In a recent meta-analysis by [27], the author describes the MPV being significantly higher in patients with stroke. Similarly, two other groups describe the MPV correlating with the prevalence and the prognosis of coronary artery disease [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent meta-analysis of 27 studies that explored MPV in stroke showed significantly higher MPV values in patients with stroke than in healthy controls. Besides, this increase persists even several months after the acute event [20]. In another study, including 3134 patients with a history of cerebrovascular disease, the authors showed an 11% increase in the relative risk of developing an acute stroke for each 1-fl of MPV increase [21].…”
Section: Arterial Diseasesmentioning
confidence: 91%